Proceedings of the 33rd ACM SIGPLAN Conference on Programming Language Design and Implementation 2012
DOI: 10.1145/2254064.2254092
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of sparse global analyses for C-like languages

Abstract: In this article we present a general method for achieving global static analyzers that are precise, sound, yet also scalable. Our method generalizes the sparse analysis techniques on top of the abstract interpretation framework to support relational as well as non-relational semantics properties for C-like languages. We first use the abstract interpretation framework to have a global static analyzer whose scalability is unattended. Upon this underlying sound static analyzer, we add our generalized sparse analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 55 publications
(121 reference statements)
0
29
0
Order By: Relevance
“…Other interesting dimensions to consider are field sensitivity [32] and widening, notably widening with thresholds. Finally, we plan to explore other effective ways to design hybrid top-down and bottom-up analysis [54], and investigate sparse inter-procedural analysis for better performance [42].…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting dimensions to consider are field sensitivity [32] and widening, notably widening with thresholds. Finally, we plan to explore other effective ways to design hybrid top-down and bottom-up analysis [54], and investigate sparse inter-procedural analysis for better performance [42].…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques handle pointers typically by staging the analysis using a pre-analysis to approximate possible definition sites and use sites [3,8,14]. However, as discussed previously, that approach cannot support reachability without sacrificing analysis precision or sparseness.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work on dataflow analysis has demonstrated that sparse analysis is a powerful technique for improving performance of many kinds of static analysis without sacrificing precision [7,8,14,15,20,21], compared to more basic dataflow analysis frameworks [12,13]. The key idea in sparse analysis is that dataflow should be propagated directly from definitions to uses in the program code, unlike "dense" analysis that propagates dataflow along the control-flow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations